(untitled) (Czech Journal of Multidisciplinary Innovations, 2025)
The Iraqi economy reinter economy that depends on the oil sector, and this led to the neglect of the other sectors and a decline in their contribution, which made its economy vulnerable to economic shocks and low development rates. SD indicators in Iraq witnessed a significant deterioration, especially during the eighties and nineties of the last century as a result of the factors as political, economic and social, as well as the wars that Iraq fought during that period and the economic blockade that Iraq was subjected to, which had a significant negative impact on most SD indicators. After the regime change in 2003 and the start of a new political and economic phase that witnessed Iraq’s transformation from following the socialist system to following the free market philosophy, some of these indicators began to gradually improve, but they are still far from the required levels .